Exploring the composition of the Pentateuch - Baker, Leslie Scott Jr.; Bergland, Kenneth; Masotti, Felipe A.; Wells, A. Rahel (Bulletin for Biblical Research Supplement, 2021)
Frontmatter -- Contents -- Preface . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . -- List of Abbreviations -- Introduction -- Contributors -- Part 1. History of Scholarship and Alternative App roaches -- Chapter 1. A Critical Intellectual History of the Historical-Critical Paradigm in Biblical Studies -- Chapter 2. The Exodus, Debt Slavery, and the Composition of the Pentateuch -- Chapter 3. Egyptian Language Practice: A Model for Hebrew Poetic Use? -- Chapter 4. Second-Millennium BC Cuneiform from the Southern Levant and the Literature of the Pentateuch -- Chapter 5. The Hittite Treaty Prologue Tradition and the Literary Structure of the Book of Deuteronomy -- Chapter 6. Memorized Covenantal Instruction and Legal Reuse in Torah -- Chapter 7. The Liturgical Function of Dates in the Pentateuch -- Part 2. Exegetical Studies -- Chapter 8. In the Tradition of Moses: The Conceptual and Stylistic Imprint of Deuteronomy on the Patriarchal Narratives -- Chapter 9. Was Moses the Last Prophet? An Analysis of a Neo-Documentarian Interpretation of Document E -- Chapter 10. Revisiting the Literary Structure(s) of Exodus -- Chapter 11. Was Leviticus Composed by Aaronide Priests to Justify Their Cultic Monopoly? -- Chapter 12. The Reception of Priestly Laws in Deuteronomy and Deuteronomy’s Target Audience -- Chapter 13. The Relevance of Ezekiel and the Samaritans for Pentateuchal Composition: Converging Lines of Evidence -- Bibliography -- Ancient Source Index -- Subject Index